Las agrupaciones corales infantiles y el desarrollo vocal musical en la ciudad de Loja. Creación de repertorio coral infantil. - Carrión Orellana, Verónica Betsabé (2023)
Children's choral repertoires include vocal compositions that have repetitive melodic motifs, simple harmonies with varied rhythms, a binary and ternary structure, and a simple language that facilitates understanding by the general public. It is important to take these characteristics into account when composing a children's choral repertoire because in this way, children's choral compositions enhance interpersonal relationships among children, provide new lexicon and serve as a teaching-learning tool for both the choral conductor and the choristers because they approach music theory through children's choral practice. The objective of this research is to contribute to children's choral groups through the creation of a children's choral repertoire that allows to enhance the musical vocal development in the city of Loja; it has a non-experimental design and is framed in the qualitative approach, also for the collection of information was used the observation sheet and the documentary review, all this in order to contribute to the investigative-compositional process and the results of the object of study. Among the most relevant results of the observation we have: that the choral conductors do not have specialization in choral conducting but in areas related to the musical labor field and that within the children's choir there is variability in certain factors such as: punctuality, intonation, rhythmic-melodic reading, pronunciation, understanding of the work, among other aspects. The lack of knowledge of children's choral repertoires at the local level is highlighted, which has caused the children's choral groups in the city of Loja to perform repetitive and habitual repertoires, limiting the choristers to experiment with a diversity of rhythms and melodies that allow them to make the most of their vocal abilities. Key words: Musical composition, Children's repertoire, Vocal skills, Children's choir, Choral conducting.